(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Ticagrelor is a new drug use to inhibit platelet aggregation induced by adenosine di phosphate (ADP) that's used to reduce atherothrombotic occurring in adults with acute coronary syndrome. Ticagrelor is class IV drug according to BCS drug classification, which is practically insoluble in water 10 μg/ml, with an absolute bioavailability of about 36 %, so this study intended to improve its water solubility and bioavailability.Method: maximum solubility of drug in different oil and co surfactant was determined and a suitable surfactant was used according to HLB system, after that a 20 formula of Ticagelor self-nano emulsion was prepared, and best formula was chosen according to different tests and subjected to an in-vivo evaluation.Results: the obtained results showed that Oleic acid, Tween 20, and Propylene glycol combination are the best constituent to prepare Ticagrelor as self-nano emulsion formula, this combination gave a large nano region upon titration with water. The best formula F5 was 10% oil and 90% surfactant -co surfactant mixture (S mix) in ratio 4:1 (tween/ Propylene glycol), showed 25 nm particle size, 0.098 polydispersity index, 10 times improvement in drug release rate than pure drug powder, and about 10 time prolongation of drug clotting time in the in-vivo study.Conclusion: the preparation of Ticagrelor as self-nano emulsion improve both the aqueous solubility of drug and the bioavailability.